Economic Operation of Low Voltage Smart Micro-grid with Integration of Renewable Energy - Kadhim Jabber; Mohammed AL-Saadi; Ameer Jaddoa (Engineering and Technology Journal, 2022)
This paper develops a unit commitment multi-period energy management system to minimize a low voltage microgrid's total operation and emission cost. The optimization problem is formulated in the mixed-integer quadratic program. The environment cost and battery degradation cost are taken into consideration in the proposed optimization approach. The unit commitment strategy is employed to minimize the total cost. A set of constraints are considered in the proposed optimization approach. The proposed energy management system is applied to the low voltage distribution grid, including different distributed generators, such as diesel engines, fuel cells, and microturbines. The microgrid also contains storage batteries, renewable energy resources, wind turbines, and photovoltaic panels. The results reveal that the storage battery charging and discharging operations are controlled to reduce the operation and emission cost even considering the battery degradation cost.